Pengetahuan Ibu tentang Manajemen Laktasi di Pukesmas Payung Sekaki Pekanbaru - isnaniar, Isnaniar; Norlita, Wiwik; Retno Novita Amelia (As-Shiha: Jurnal Kesehatan, 2022)
Knowledge is the result of "knowing" and this occurs after peoplehave sensed a certain object. Lactation management is a necessary management to support successful breastfeeding. Things that need to be prepared in lactation management during pregnancy are mothers seeking information about the advantages of breastfeeding, the benefits of breastfeeding and the negative impact of formula feeding, mothers check their health during pregnancy, nipple conditions breasts and monitor weight gain during pregnancy, perform breast care since 6 months of pregnancy, mothers seek information about nutrition and additional food during pregnancy. Exclusive Breast Milk (ASI) based on Government Regulation Number of 2012 is breast milk that is given to babies from birth for 6 months. The implementation of breastfeeding can be done properly and correctly if there is complete information about the benefits of breastfeeding and breastfeeding as well as lactation management. Research Objectives: To find out the description of mother's knowledge about lactation management at Payung Sekaki Health Center Pekanbaru. Research: The type of research used is descriptive, the sampling technique is purposive sampling. The data collection method used a questionnaire and was carried out from 21 July to 10 August 2022, with 50 respondents. Research Results: Proving that the description of mother's knowledge about lactation management is in the good category, 14 respondents (28%), enough for 16 respondents (32%), while less than 20 respondents (40%). Conclusion: Based on the results of this study, the researcher hopes that mothers can increase their knowledge about lactation management starting from pregnancy, childbirth and breastfeeding. Health workers should be more active in providing information about the benefits of lactation management.